A Matter of Taste: Lineage-Specific Loss of Function of Taste Receptor Genes in Vertebrates - Antinucci, Marco; Risso, Davide (Frontiers in Molecular Biosciences, 2017)
Vertebrates can perceive at least five different taste qualities, each of which is thought to have a specific role in the evolution of different species. The avoidance of potentially poisonous foods, which are generally bitter or sour tasting, and the search for more nutritious ones, those with high-fat and high-sugar content, are two of the most well-known examples. The study of taste genes encoding receptors that recognize ligands triggering taste sensations has helped to reconstruct several evolutionary adaptations to dietary changes. In addition, an increasing number of studies have focused on pseudogenes, genomic DNA sequences that have traditionally been considered defunct relatives of functional genes mostly because of the presence of deleterious mutations interrupting their open reading frames. The study of taste receptor pseudogenes has helped to shed light on how the evolutionary history of taste in vertebrates has been the result of a succession of gene gain and loss processes. This dynamic role in evolution has been explained by the “less-is-more” hypothesis, suggesting gene loss as a mechanism of evolutionary change in response to a dietary shift. This mini-review aims at depicting the major lineage-specific loss of function of taste receptor genes in vertebrates, stressing their evolutionary importance and recapitulating signatures of natural selection and their correlations with food habits.